HGMB1 and RAGE as Essential Components of Ti Osseointegration Process in Mice - Biguetti, Claudia Cristina; Cavalla, Franco; Silveira, Elcia Varize; Tabanez, André Petenuci; Francisconi, Carolina Favaro; Taga, Rumio; Campanelli, Ana Paula; Trombone, Ana Paula Favaro; Rodrigues, Danieli C.; Garlet, Gustavo Pompermaier (Frontiers in Immunology, 2019)
The release of the prototypic DAMP High Mobility Group Box 1 (HMGB1) into extracellular environment and its binding to the Receptor for Advanced Glycation End Products (RAGE) has been described to trigger sterile inflammation and regulate healing outcome. However, their role on host response to Ti-based biomaterials and in the subsequent osseointegration remains unexplored. In this study, HMGB1 and RAGE inhibition in the Ti-mediated osseointegration were investigated in C57Bl/6 mice. C57Bl/6 mice received a Ti-device implantation (Ti-screw in the edentulous alveolar crest and a Ti-disc in the subcutaneous tissue) and were evaluated by microscopic (microCT [bone] and histology [bone and subcutaneous]) and molecular methods (ELISA, PCRarray) during 3, 7, 14 and 21 days. Mice were divided into 4 groups: Control (no treatment); GZA (IP injection of Glycyrrhizic Acid for HMGB1 inhibition, 4mg/Kg/day); RAP (IP injection of RAGE Antagonistic Peptide, 4mg/Kg/day), and vehicle controls (1.5% DMSO solution for GZA and 0.9% saline solution for RAP); treatments were given at all experimental time points, starting 1 day before surgeries. HMGB1 was detected in the Ti-implantation sites, adsorbed to the screws/discs. In Control and vehicle groups, osseointegration was characterized by a slight inflammatory response at early time points, followed by a gradual bone apposition and matrix maturation at late time points. The inhibition of HMGB1 or RAGE impaired the osseointegration, affecting the dynamics of mineralized and organic bone matrix, and resulting in a foreign body reaction, with persistence of macrophages, necrotic bone and foreign body giant cells until later time points. While Control samples were characterized by a balance between M1 and M2-type response in bone and subcutaneous sites of implantation, and also MSC markers, the inhibition of HMGB1 or RAGE caused a higher expression M1 markers and pro-inflammatory cytokines, as well chemokines and receptors for macrophage migration until later time points. In conclusion, HMGB1 and RAGE have a marked role in the osseointegration, evidenced by their influence on host inflammatory immune response, which includes macrophages migration and M1/M2 response, MSC markers expression, which collectively modulate bone matrix deposition and osseointegration outcome.